Microtubule-dependent path to the cell cortex for cytoplasmic dynein in mitotic spindle orientation - Markus, Steven M. (Landes Bioscience, 2011)
During animal development, microtubules (MTs) play a major role in directing cellular and subcellular patterning, impacting cell polarization and subcellular organization, thereby affecting cell fate determination and tissue architecture. In particular, when progenitor cells divide asymmetrically along an anterior-posterior or apical-basal axis, MTs must coordinate the position of the mitotic spindle with the site of cell division to ensure normal distribution of cell fate determinants and equal sequestration of genetic material into the two daughter cells. Emerging data from diverse model systems have led to the prevailing view that, during mitotic spindle positioning, polarity cues at the cell cortex signal for the recruitment of NuMA and the minus-end directed MT motor cytoplasmic dynein.(1) The NuMA/dynein complex is believed to connect, in turn, to the mitotic spindle via astral MTs, thus aligning and tethering the spindle, but how this connection is achieved faithfully is unclear. Do astral MTs need to search for and then capture cortical NuMA/dynein? How does dynein capture the astral MTs emanating from the correct spindle pole? Recently, using the classical model of asymmetric cell division—budding yeast S. cerevisiae—we successfully demonstrated that astral MTs assume an active role in cortical dynein targeting, in that astral MTs utilize their distal plus ends to deliver dynein to the daughter cell cortex, the site where dynein activity is needed to perform its spindle alignment function. This observation introduced the novel idea that, during mitotic spindle orientation processes, polarity cues at the cell cortex may actually signal to prime the cortical receptors for MT-dependent dynein delivery. This model is consistent with the observation that dynein/dynactin accumulate prominently at the astral MT plus ends during metaphase in a wide range of cultured mammalian cells.